Combination of vortex assisted binary solvent microextraction and QuEChERS for the determination of prothiofos, oxadiargyl, and gamma-cyhalothrin in water and pineapple samples by gas chromatography mass spectrometry - Budak, Turkan Borklu; Ayyildiz, Merve Firat; Chormey, Dotse Selali; Bakirdere, Sezgin (SPRINGER, 2020)
An accurate and sensitive dispersive liquid-liquid microextraction method based on binary solvents was used to enrich prothiofos, oxadiargyl, and gamma-cyhalothrin for quantification by GC-MS. The combination of two extraction solvents (binary mixture) resulted in higher extraction efficiencies compared to the single solvent extraction systems. Parameters of the binary extraction method where optimized to enhance the extraction output of the analytes. The limits of detection calculated for the analytes ranged between 0.59 and 1.6 ng/mL. Linear calibration plots of the analytes covered wide concentration ranges with R-2 values greater than 0.9996 and percent relative standard deviation lower than 10%. Spiked recovery experiments were performed well and wastewater at two different concentrations and satisfactory results (89-104%) were obtained. The binary solvent microextraction method was combined with QuEChERS to quantify the analytes in pineapple matrix, using matrix matching method to enhance the accuracy of the method to almost 100%.
Keywords: Pesticides; Binary solvent microextraction; GC-MS; Prothiofos; Oxadiargyl; Gamma-cyhalothrin; LIQUID-LIQUID MICROEXTRACTION; PESTICIDE-RESIDUES; EXTRACTION; Environmental Sciences & Ecology